Compliance and the enforcement of EU law - Cremona, Marise (Oxford : Oxford University Press, 2012)
The EU has long faced difficulties in ensuring compliance with its legal provisions, and as a result has developed enforcement techniques that penetrate deep into the law and politics of member states. This book gathers leading experts to assess the legal procedures and political mechanisms at work in the EU to promote compliance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- European Union countries; Effectiveness and validity of law -- European Union countries; Law enforcement -- European Union countries